2007
DOI: 10.1007/s00586-007-0433-8
|View full text |Cite
|
Sign up to set email alerts
|

Value of predictive instruments to determine persisting restriction of function in patients with subacute non-specific low back pain. Systematic review

Abstract: Low back pain (LBP) can restrict function with all the personal, interpersonal, and social consequences, such as a loss of independence and the inability to fulfil diverse roles in social life. Therefore, the prevention of the consequences of LBP would reduce costs, individual burdens and social burdens. Being able to fulfil the requirements of daily living is a cornerstone of quality of life. Early identification of patients who are likely to develop chronic pain with persistent restricted function is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 46 publications
(73 reference statements)
3
37
0
5
Order By: Relevance
“…Es ist zu vermuten, dass ein häufig mit Übergewicht verbundener Lebensstil, der allerdings erheblich komplizierter zu erheben ist, möglicherweise relevanter ist als das Übergewicht an sich. Die Relevanz der Depressivität im Hinblick auf den Therapieerfolg kommt in der Literatur zu sehr heterogenen Ergebnissen und zeigt sich in einer Metaanalyse nicht als studienübergreifender Prädik-tor [9]. Eine weitere Metaanalyse sieht als Vorhersage der Beeinträchtigung nach 12 Monaten B SE B beta Konstante -5,68 2,65 Alter 0,02 0,02 0,08 Geschlecht 0,12 0,39 0,03 Schmerzintensität 0, gut belegt an, dass Depression kein Prä-diktor für eine Rückkehr an den Arbeitsplatz ist [11].…”
Section: Abb 2 8 Ausmaß Der Beeinträchtigung Im Verlauf Prä Vor Derunclassified
See 2 more Smart Citations
“…Es ist zu vermuten, dass ein häufig mit Übergewicht verbundener Lebensstil, der allerdings erheblich komplizierter zu erheben ist, möglicherweise relevanter ist als das Übergewicht an sich. Die Relevanz der Depressivität im Hinblick auf den Therapieerfolg kommt in der Literatur zu sehr heterogenen Ergebnissen und zeigt sich in einer Metaanalyse nicht als studienübergreifender Prädik-tor [9]. Eine weitere Metaanalyse sieht als Vorhersage der Beeinträchtigung nach 12 Monaten B SE B beta Konstante -5,68 2,65 Alter 0,02 0,02 0,08 Geschlecht 0,12 0,39 0,03 Schmerzintensität 0, gut belegt an, dass Depression kein Prä-diktor für eine Rückkehr an den Arbeitsplatz ist [11].…”
Section: Abb 2 8 Ausmaß Der Beeinträchtigung Im Verlauf Prä Vor Derunclassified
“…In einer systematischen Übersicht zu Studien mit dem Ziel der Analyse von Risikofaktoren für einen ungünstigen Verlauf wird eine Varianzaufklärung von bis zu 51% berichtet [9]. Somit liegt die Vorhersagekraft der Regressionsmodelle im unteren Bereich.…”
Section: Tab 4 Ergebnisse Der Linearen Regression Zurunclassified
See 1 more Smart Citation
“…However despite the weight of evidence there remains a tendancy to rely on instruments that quantify prognostic factors from a biomedical perspective alone, rather than the contemporary biopsychosocial model, whilst focusing on return to work as a single outcome. A predictive instrument that may help clinicians fully incorporate the biopsychosocial model into clinical practice clearly has some utility, and whilst it has been suggested that such an instrument needs to capture all the potential biopsychosocial risk factors that may adversely affect functional outcomes (Hilficker, Bachmann, et al 2007), an initial attempt to produce such a draft questionnaire resulted in a long and unwieldy instrument www.intechopen.com…”
Section: Introductionmentioning
confidence: 99%
“…This makes the early identification of modifiable factors of the progression of acute/subacute LBP to the persistent state essential, especially in working populations [3,4,5]. The differentiation of these modifiable factors into protective versus risk factors for the development of persistent LBP should be considered [6,7].…”
Section: Introductionmentioning
confidence: 99%